Polyostotic Fibrous Dysplasia With and Without McCune–Albright Syndrome—Clinical Features in a Nordic Pediatric Cohort - Utriainen, Pauliina; Valta, Helena; Björnsdottir, Sigridur; Mäkitie, Outi; Horemuzova, Eva (Frontiers in Endocrinology, 2018)
Objective: Fibrous dysplasia (FD) presents as skeletal lesions in which normal bone is replaced by abnormal fibrous tissue due to mosaic GNAS mutation. McCune-Albright syndrome (MAS) refers to FD combined with skin (café-au-lait) and endocrine manifestations. This study describes the clinical childhood manifestations of polyostotic FD and MAS in a Nordic cohort. Patients and design: We retrospectively reviewed a cohort of pediatric patients (n=16) with polyostotic FD with or without MAS diagnosed and followed in two Nordic Pediatric tertiary clinics between 1996 - 2017. Results: Half of the 16 patients with polyostotic FD presented with MAS. All patients with MAS (n=8) had café-au-lait spots, and either gonadotropin-independent precocious puberty (girls; n=5) or abnormal testicle structure (boys, n=3). None manifested hyperthyroidism or growth hormone excess. Mild hypophosphatemia was common (11/16), but none had signs of hypophosphatemic rickets. Craniofacial bone involvement was found in 12 patients (75 %); in five of these, skeletal lesions were limited to craniofacial area. One child with craniofacial disease had lost vision due to optic nerve damage. Eleven (69 %) patients had sustained a fracture at FD lesion, over half of them requiring surgical fixation of the fracture, most commonly in the proximal femur. The first symptoms leading to FD/MAS diagnosis included skull/facial asymmetry (n=4), precocious puberty (n=3), abnormal gait (n=3), pathologic fracture (n=3), wide-spread café-au-lait spots (n=1), headache (n=1) and vision loss (n=1). Conclusions: Polyostotic FD and MAS remain diagnostic and therapeutic challenges because of the broad clinical spectrum. Recurrent fractures, pain, and even vision loss, may impair the quality of life in children with FD.